Resilient networks and quality of life - Delle Cave, Luigi (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
The contribution presents the results of a research conducted in the historic center of Naples on the theme of quality of life and social resilience. Recovering the dimensions of the BES (“BenessereEquo e Sostenibile”, Fair and Sustainable Wellness), the results of a survey created with the aim of identifying a series of indicators focused on the crucial aspects that (directly or indirectly) influence and determine the level of well-being of individuals and local communities in the historic center of Naples. On the other hand, the contribution offers a reflection on the ability of citizens to respond to social problems, showing practices of social resilience "mediated" sometimes by the contribution offered by small local organizations (many of them volunteering); sometimes by initiatives proposed by groups of citizens who, in a self-organized and spontaneous way, activate a dense fabric of "informal" relationships in the territory, made up of particularly active and enterprising small knot networks. We have defined them as resilient networks: networks that show the elasticity of the social body to respond to uncomfortable situations, to restore forgotten and disused places to citizens, to amplify (even indirectly) the perception of citizens’ quality of life, giving value to initiatives that lead to the rediscovery of old and new urban spaces.